PENGARUH KOMPETENSI PEDAGOGIK DAN MOTIVASI BERPRESTASI TERHADAP KINERJA GURU - Prayogi, Rachmad Agung Prayogi (STISIP Widyapuri Mandiri Sukabumi, 2025)
This study was inspired by the phenomenon of low teacher performance which is reflected in the low ability to meet predetermined standards. This study aims to analyse and determine: a) the effect of pedagogical competence on teacher performance; b) the effect of achievement motivation on teacher performance; c) the effect of pedagogical competence and achievement motivation on teacher performance in Pontianak City. The problem in this study is the low level of teacher pedagogic competence and the low level of teacher achievement motivation that affects the performance of a teacher and has an impact on students in the learning process. The research approach used is quantitative research with survey method. The type of data consists of primary and secondary data, data collection tools using questionnaires distributed to respondents who are taken proportionally. Data is processed using parametric statistics. Hypothesis testing using the R test, T test and F test. The results of data processing and analysis show that pedagogical competence and achievement motivation both partially and simultaneously have a significant effect on teacher performance. The conclusion is that pedagogical competence and achievement motivation have a significant effect on teacher performance.